Synchronous and metachronous colorectal liver metastases: impact of primary tumor location on patterns of recurrence and survival after hepatic resection: Colorectal liver surgery and prognosis - Garajova, Ingrid; Balsano, Rita; Tommasi, Chiara; Dalla Valle, Raffaele; Pedrazzi, Giuseppe; Ravaioli, Matteo; Spallanzani, Andrea; Leonardi, Francesco; Santini, Chiara; Caputo, Francesco; Riefolo, Mattia; Giuffrida, Mario; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background:Considerable differences in terms of prognosis exist between the right-sided (RCC) and the left-sided colon cancer (LCC). Aim of the work: In this study, we evaluated prognostic implications of primary tumor location (PTL) among patients who underwent curative-intent hepatectomy for synchronous (SM) and metachronous (MM) colorectal liver metastases (CRLM).Methods:The study population included all consecutive patients affected by CRLM scheduled for first liver resection at three Italian oncological centers. Results:A total of 204 patients who underwent CRLM resection were included, 50% with RCC. Synchronous lesions were prevalent (n=133, 65%). Median OS was respectively 40.3 months for SM-RCC, 53.5 months for SM-LCC, 64.5 months for MM-RCC and 81.6 months for MM-LCC. Patients with MM-LCC showed an OS better than patients with SM-RCC (p=0.008) and SM-LCC (p=0.002). PTL had no influence on RFS. RCC group had less recurrences (75% vs 86.5%), though further surgery with curative-intent was possible more in LCC group (29.3% vs 32.5%). Cox proportional hazards model analysis showed that age and the presence of SM vs MM was associated with a significantly higher hazard ratio (HR) for death (HR=1.024; 95%CI=1.005-1.043; p=0.011 and HR=2.010; 95%CI=1.328-3.043; p=0.001, respectively). Conclusions:We confirmed that patients with CRLM and right-sided primary colon cancer experience worse survival after hepatic resection. The timing of metastasis has been revealed as important prognostic factor.